2011
DOI: 10.1590/s0102-09352011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre dois protocolos para obtenção de plasma rico em plaquetas, em cães

Abstract: RESUMOAvaliaram-se dois protocolos para a produção de plasma rico em plaquetas (PRP) com o sangue de 20 cães adultos. Foram coletados três frascos de sangue em que um deles foi usado para produção do PRP por meio do protocolo A − centrifugação única a 1200rpm/10min −, o outro para fabricação do PRP pelo protocolo B − primeira centrifugação a 1200rpm/10min e a segunda centrifugação a 1600rpm/10min − e o terceiro para realização da contagem plaquetária no sangue total, que serviu de parâmetro para os valores alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
4
0
4
Order By: Relevance
“…In order to obtain PRP, we performed double centrifugation with adequate rotation force to avoid the premature release of the GF in the platelets 20 , and thus, promoted its action in the wound repair process. Platelet activation by the addition of 10% calcium gluconate immediately prior to the treatment of these lesions ensured, as indicated by Maia et al 9 , a suitable concentration of these factors in the PRP, the most important of which are TGF-β, PDGF, and IGF-I 4 .…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain PRP, we performed double centrifugation with adequate rotation force to avoid the premature release of the GF in the platelets 20 , and thus, promoted its action in the wound repair process. Platelet activation by the addition of 10% calcium gluconate immediately prior to the treatment of these lesions ensured, as indicated by Maia et al 9 , a suitable concentration of these factors in the PRP, the most important of which are TGF-β, PDGF, and IGF-I 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The protocols were selected for being simple, low-cost, and efficient at concentrating platelets (ALEIXO et al, 2011;KIM et al, 2002). However, leukocytes and red blood cells were not evaluated in previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…The microscopic morphological visualization of platelets using a PRP smear is recommended to evaluate the quality of the blood component, since pseudopods are formed after activation (WEISS; WARDROP, 2010), releasing growth factors in advance (EPPLEY et al, 2004). A previous study showed no morphological changes in PRP platelets obtained by direct microscopy (ALEIXO et al, 2011). However, a study using electronic microscopy to visualize platelet morphology in PRP detected 49% of platelets with uncertain activation, 41% at rest, 9% activated, and 1% damaged (ZANDIN et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Na medicina humana, estão disponíveis vários sistemas de separação comercial para a preparação do PRP, porém as concentrações de componentes sanguíneos sofrem variações substanciais entre esses sistemas (OUDELAAR et al, 2019). Na veterinária, não há uma padronização da técnica para a produção de PRP em cães e diferentes métodos têm sido utilizados visando encontrar uma melhor concentração com a preservação das propriedades plaquetárias (FERRAZ et al, 2007;ALEIXO et al, 2011;VANAT et al, 2012, PENHA et al, 2014.…”
Section: Introducãounclassified